PENGARUH KONSELING KELOMPOK TERHADAP PENURUNAN KECEMASAN KOMUNIKASI SISWA KELAS X SMA NEGERI 2 SIAKHULU T.P. 2014/2015 - Ria Candrawati Candrawati; Raja Arlizon Arlizon; Zulfan Saam Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Communication is very important for students as a bridge for searching and understanding information. In reality, not all students can communicate effectively. It is characterized by the emergence of communication anxiety symptoms, such as nervous, shaky, and scared. As a result, it will be difficult for students to handle the depressing situations so that students can’t develop the knowledge that they got well. Furthermore, they will be assumed as passive students. The objective of this research was: 1) to describe students’ communication anxiety before Group Counseling was applied. 2) to describe the process of Group Counseling implementation to reduce students’ communication anxiety. 3) to describe students’ communication anxiety after Group Counseling was applied. 4) to identify students’ communication anxiety differentiation before and after Group Counseling was applied. 5) to identify the effect of group counseling on communication anxiety reduction. This research was pre-experimental research with one-group pre-test post-test desaign. The subject of this research was 30 students who have communication anxiety. Correlational test hypothesis of this research was rejected because the result the data analysis indicates that rcount was smaller than rtable (0,314 < 0,361). It showed that there was no significant positive effect of Group Counseling on students’ communication anxiety reduction. The scale of the effect on interpretation table was on low level (9,8%). In contrary, regression test hypothesis of this research was accepted because the result the data analysis indicates that tcount was bigger than ttable (7,385<2,000). In conclusion, it showed that there was asignificant effect of Group Counseling on students’ communication anxiety reduction. Keyword : Group Counseling, Anxiety Communication